Contemporary Amharic Oral Poetry from Gojjam: Classification and a sample Analysis - Gelaye, Getie (Aethiopica, 1999)
In the preceding discussion, an attempt was made to provide a classification of Amharic oral poems and songs into several themes and genres. Accordingly, such major genres as work songs, children’s poems, war chants and boasting recitals were identified and a description and analysis of selected poems and their role, particularly in local politics and administration, were provided. In their poems and songs, the peasants of East Gojjam critically express their views, attitudes and feelings either in the form of support or protest, towards the various state policies and local directives. Indeed, the Amharic oral poems and songs from the two peasant communities illustrate topics associated with the change of government, land redistribution, local authorities and their administration, as well as a variety of other contemporary issues affecting the rural society. The poems also throw some light on the understanding of the peasants’ consciousness and observations comparing past and present regimes of Ethiopia, besides their power of aesthetics and creative capabilities of the peasants’ poetic tradition. In fact, this can be seen from a wider perspective, considering the function and role of oral literature in an agrarian and traditional society such as the two peasant communities mentioned in this paper. The peasants’ response in poetry to the diverse contemporary politics and local administration need to be studied carefully and considered appropriately in the state’s future rural policies and development projects if it is intended to bring about a democratic system that leads towards a peaceful coexistence among the rural peasantry.